2021
DOI: 10.3389/fpsyg.2021.691438
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Social and Behavioral Characteristics to Suicidality in Community Adolescents With Self-Harm: Considering Contagion and Connection on Social Media

Abstract: A close link has been established between self-harm and suicide risk in adolescents, and increasing attention is given to social media as possibly involved in this relationship. It is important to identify indicators of suicidality (i.e., suicide ideation or attempt) including aspects related to contagion in online and offline social networks and explore the role of social media in the relationship between social circumstances and suicidality in young adolescents with self-harm. This study explored characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…[13][14][15][16][17]62 Although more research is needed, sex-and gender-specific stressors may be associated with the pandemic such as a differential or gendered response to less in-person contact with peers and social networks, 63 cessation of in-person mental health support services, 60 more time on social media 64,65 opportunity for social comparison [66][67][68] -and access to online communities that perpetuate self-harm contagion. [68][69][70][71] Findings from this study should be interpreted in the context of well-established sex differences in psychiatric epidemiology among youth, including the preponderance of depression, [72][73][74] higher reported prevalence of self-harm 75,76 and more suicide attempts and mental health service use among adolescent females, 77,78 all of which were trending upward before the pandemic. [79][80][81][82][83][84][85] Indeed, younger females were the largest group of new users of acute mental health services in this study, which speaks to their baseline vulnerability.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[13][14][15][16][17]62 Although more research is needed, sex-and gender-specific stressors may be associated with the pandemic such as a differential or gendered response to less in-person contact with peers and social networks, 63 cessation of in-person mental health support services, 60 more time on social media 64,65 opportunity for social comparison [66][67][68] -and access to online communities that perpetuate self-harm contagion. [68][69][70][71] Findings from this study should be interpreted in the context of well-established sex differences in psychiatric epidemiology among youth, including the preponderance of depression, [72][73][74] higher reported prevalence of self-harm 75,76 and more suicide attempts and mental health service use among adolescent females, 77,78 all of which were trending upward before the pandemic. [79][80][81][82][83][84][85] Indeed, younger females were the largest group of new users of acute mental health services in this study, which speaks to their baseline vulnerability.…”
Section: Discussionmentioning
confidence: 66%
“… 13 17 , 62 Although more research is needed, sex-and gender-specific stressors may be associated with the pandemic such as a differential or gendered response to less in-person contact with peers and social networks, 63 cessation of in-person mental health support services, 60 more time on social media 64 , 65 — which may present more opportunity for social comparison 66 68 — and access to online communities that perpetuate self-harm contagion. 68 71 …”
Section: Discussionmentioning
confidence: 99%
“…A survey explored the characteristics of Korean adolescents with a recent history of self-harm. This study showed that having friends who self-harm was associated with an increased likelihood of lifetime suicidality [ 29 ▪ ]. Another study showed that adolescents with a suicide attempt who sought outpatient or emergency mental healthcare were more likely to affiliate with suicidal peers compared to their matched controls [ 30 ▪ ], while another study showed that knowing a peer who had attempted suicide was associated with a transition from suicidal ideation to a planned suicide attempt [ 31 ▪ ].…”
Section: Social Contagion and Suicidementioning
confidence: 99%
“…Previous studies on SI in South Korea have identi ed associations with female gender, lower socioeconomic status, and psychiatric conditions [20][21][22]. However, these studies often focused primarily on the adolescent population [22][23][24][25][26][27][28][29][30][31][32][33][34][35], limiting the generalizability of the ndings to all age groups. Additionally, many relied on web-based questionnaires [25,29] or small-size clinical data [30,36,37].…”
Section: Introductionmentioning
confidence: 99%